Every bone tells a story : Hominin discoveries, deductions, and debates - Rubalcaba, Jill (Charlesbridge, 2010)
Discusses the unearthing of four hominins--Turkana Boy, Lapedo Child, Kennewick Man, and Iceman--and the ways that new technology has helped archaeological specialists to refine their theories and change their view of the past.